IoT-Based BLE Architecture for Interactive Information Sharing in Resource-Constrained Educational Environments (Architecture Image Studies, 2025)
This study, based on the advancement of existing smart city convergence content, installed Low-power Bluetooth Beacon Sensors inside the campus of G University in Gyeonggi-do, South Korea, and built the IoT-based environment to build the infrastructure network where users can effectively share information within the campus in the form of interaction through short-range communication. Thus, it realized a future university infrastructure environment by super-connecting the university campus with Local Area Network to manage data and share important information generated on campus with members and users. In addition, it conducted the test-bed for the Integrated Information Sharing Platform of the Campus Environment built in this study and verified its excellence by analyzing the Efficiency, Stability, and Effectiveness of the Infrastructure Construction centered on users. The greatest strength of this Platform is that it can minimize infrastructure costs. If it is applied to universities in developing countries and underdeveloped regions overseas as well as domestically in the future, it is expected that a competitive campus environment can be established.